Associations between serum lipid levels and the macular retinal volumes in patients with diabetes - Yasuaki Mushiga; Norihiro Nagai; Yoko Ozawa (PLoS ONE, 2025)
Purpose Macular retinal volumes can be measured by optical coherence tomography (OCT). However, the underlying pathogenesis was obscure. We compared the OCT and serum lipid data in participants with or without diabetes mellitus (DM) and diabetic retinopathy (DR) to explore the interpretation of the OCT data. Methods Data for eye examinations and blood tests in 41 eyes of 41 participants (23 men; mean age 49.1 ± 8.3) were analyzed. Eyes without macular lesions were included. Results Mean macular retinal volumes of ganglion cell layer (GCL) (P = 0.023) and neural retinal layers (NRL) including layers from internal to external limiting membranes (P = 0.013) were smaller in the DM without DR group than in the control group. Mean serum malondialdehyde-modified low-density lipoprotein (MDA-LDL) levels were higher in the DM without DR (P = 0.046) and with DR (P = 0.021) groups than in the control group. Serum low-density lipoprotein cholesterol (LDLC) levels showed a negative correlation with GCL volume (P = 0.005), and trends of negative correlations with retinal nerve fiber layer (RNFL) (P = 0.060) and NRL volumes (P = 0.051) in the control group. However, in the DM with DR group, LDLC levels showed significant positive correlations with RNFL (P = 0.002), GCL (P = 0.034), and NRL (P = 0.002) volumes. The DR group also showed positive correlations between MDA-LDL levels and RNFL (P < 0.001) and NRL (P = 0.006) volumes. Conclusions Macular retinal volumes may decrease owing to DM and elevated serum lipid levels. However, the volume may increase as serum lipid levels elevate after DR development. Further studies are warranted to understand the pathogenesis.